2018
DOI: 10.4078/jrd.2018.25.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Process of Conducting Meta-analyses of the Diagnostic Test Accuracy

Abstract: Diagnosis is a critical step for clinical treatment. Many individual studies have been conducted to determine the accuracy of various diagnostic tests, but they had small sample sizes and correspondingly inadequate statistical strength. Combining the results from several such studies can help increase the statistical strength and precision of their results. Meta-analysis is a useful tool for evaluating the accuracy of diagnostic tests and can be used to obtain precise estimates when multiple small studies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…As further summary measures, we calculated positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio using the pooled sensitivity and specificity. The results described in the HSROC curve included 95% prediction and 95% confidence regions [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…As further summary measures, we calculated positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio using the pooled sensitivity and specificity. The results described in the HSROC curve included 95% prediction and 95% confidence regions [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hierarchical regression based on a random-effects model was used to synthesize the TP, FP, TN, and FN values (Kim et al, 2015; Lee, 2018). This bivariate approach considers the potential between-study heterogeneity by accommodating the correlation between sensitivity and specificity in each study (Kim et al, 2015; Lee, 2018; Lee et al, 2015). Furthermore, unlike the traditional method of using straight lines to indicate pooled estimates, this approach generates an ellipse for pooled mean sensitivity and specificity, along with their 95% confidence intervals (CI).…”
Section: Methodsmentioning
confidence: 99%
“…As summary measures, a diagnostic odds ratio, positive likelihood ratio, and negative likelihood ratio were calculated using the pooled sensitivity and specificity. The results of the meta‐analyses were presented in HSROC curve, which included 95% confidence and 95% prediction regions (Lee, Kim, Choi, Huh, & Park, 2015; Lee, 2018). We also performed subgroup analysis according to the cut‐off value because four of the included studies reported the DTA of the Nu‐DESC by using various cut‐off scores (Hargrave et al., 2017; Leung et al., 2008; Neufeld et al., 2013; Saller et al., 2019).…”
Section: The Reviewmentioning
confidence: 99%